Phase 2 study of imexon, a prooxidant molecule, in relapsed and refractory B-cell non-Hodgkin lymphoma - Barr, Paul M; Miller, Thomas P; Friedberg, Jonathan W; Peterson, Derick R; Baran, Andrea M; Herr, Megan; Spier, Catherine M; Cui, Haiyan; Roe, Denise J; Persky, Daniel O; Casulo, Carla; Littleton, Jamie; et al. (Blood, 2014)
Lymphoma cells are subject to higher levels of oxidative stress compared with their normal counterparts and may be vulnerable to manipulations of the cellular redox balance. We therefore designed a phase 2 study of imexon (Amplimexon/NSC-714597), a prooxidant molecule, in patients with relapsed/refractory B-cell non-Hodgkin lymphoma (NHL). Imexon was administered at 1000 mg/m(2) IV daily for 5 days in 21-day cycles. Gene expression analysis performed on pretreatment tumor specimens included 13 transcripts used to generate a redox signature score, previously demonstrated to correlate with lymphoma prognosis. Twenty-two patients were enrolled having follicular (n = 9), diffuse large B-cell (DLBCL) (n = 5), mantle cell (n = 3), transformed follicular (n = 2), small lymphocytic (n = 2), and Burkitt (n = 1) lymphoma. The most common grade 3/4 adverse events were anemia (14%) and neutropenia (9%). The overall response rate was 30%, including responses in follicular lymphoma (4 of 9) and DLBCL (2 of 5). Gene expression analyses revealed CD68 and the redox-related genes, GPX1 and SOD2, as well as a higher redox score to correlate with clinical responses. Therefore, pretreatment markers of oxidative stress may identify patients likely to respond to this therapeutic approach. This trial was registered at www.clinicaltrials.gov as #NCT01314014.